Electrophoretic migration of organophosphorus pesticides as a function of separation potential in micellar electrokinetic chromatography : a basis of predicting the retention factors - W. Ibrahim, W. Aini; Monjurul Alam, S. M.; Sulaiman, A. B. (Penerbit UTM Press, 2004)

(untitled)
Retention Factors (K2) In Micellar Electrokinetic Chromatography (MEKC) Are Very Often Calculated Against The Mobility Of Fully Retained Hydrophobic Micelle Markers, Which Are Not Abundant For Universal Use. An Alternative Approach Was Proposed To Predict The K2 Values On The Basis Of A Functional Relationship Between The Solutes Retention Times And Separation Potentials Using Organophosphorus Pesticides (Opps) As Reference Hydrophobic Compounds. The Use Of The Proposed Simple Linear Model Was Evaluated For Another Set Of Hydrophilic Opps And Its Practicality Was Defined.